Butane-2,3-diacetal-desymmetrized glycolic acid—a new building block for the stereoselective synthesis of enantiopure α-hydroxy acids - Díez, E; Dixon, D; Ley, S (Wiley-VCH, 2001)
According to a chiral memory protocol, a chiral glycolic acid equivalent, the butane-2,3-diacetal-desymmetrized glycolate 2, is obtained from chiral 3-halopropane-1,2-diols 1. Compound 2 is a new and effective building block for the synthesis of mono- and dialkylated α-hydroxy acids 3, which constitute a biologically and pharmacologically important structural motif.